2007
DOI: 10.1097/01.tp.0000287541.53389.be
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Monocarboxylate Transporter-1 (MCT-1) Inhibitor, AR-C117977, Induces Donor-Specific Suppression, Reducing Acute and Chronic Allograft Rejection in the Rat

Abstract: This report describes a MCT-1 specific inhibitor having immunosuppressive activity on alloimmune responses and inducing donor-specific suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…A new class of specific and extremely high-affinity inhibitors of MCT1 have been discovered by AstraZeneca [3537]. We have confirmed the ability of one of these inhibitors, AR-C155858, to inhibit MCT1 in rat erythrocytes with a K i value of approx.…”
Section: Introductionsupporting
confidence: 63%
“…A new class of specific and extremely high-affinity inhibitors of MCT1 have been discovered by AstraZeneca [3537]. We have confirmed the ability of one of these inhibitors, AR-C155858, to inhibit MCT1 in rat erythrocytes with a K i value of approx.…”
Section: Introductionsupporting
confidence: 63%
“…Interestingly, these extracellular α-syn aggregates can then transfer from neuron to neuron or from neuron to glial cell 105 where they can nucleate further intracellular aggregation and/or trigger neuro-inflammation and exacerbate the neurodegenerative process 69, 108 . Supporting the potential relevance of this process in the pathogenesis of α-synucleinopathies, previous studies have shown accumulation of α-syn in fetal grafted neurons in patients with PD 109, 110 , as well as in grafted neuronal precursor cells in the hippocampus 69 and basal ganglia 111 in mouse models. Interestingly, α-syn has also been shown to ectopically accumulate in oligodendroglial cells in multiple system atrophy (another synucleinopathy) 112 and in astroglial cells in PD 113, 114 .…”
Section: α-Synuclein and Diseasementioning
confidence: 72%
“…Previously, a new class of specific and extremely potent inhibitors of MCT1 have been discovered by AstraZeneca that were reported to show no binding to MCT4 and exhibit lower-affinity binding to MCT2 [3032]. The K d values for these inhibitors binding to endogenous MCT1 in rat and human cells was found to be in the low nanomolar region or less, as was also found for MCT1 expressed in Ins-1 cells that contain little or no endogenous MCT1 [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, this agent is at least two orders of magnitude more potent at inhibiting the mitochondrial pyruvate carrier than MCT1 [2629]. Previously, a new class of specific and extremely high-affinity inhibitors of MCT1 have been discovered by AstraZeneca [3032]. These compounds were originally identified as potent inhibitors of T-lymphocyte proliferation that act as immunosuppressants and were subsequently shown to bind to MCT1 and MCT2, but not MCT4 [30].…”
Section: Introductionmentioning
confidence: 99%